LINGUISTIC ASPECTS OF FANTASY STORY TEXTS IN CLASS 7 MIDDLE SCHOOL TEACHING MATERIALS - Sopani, Ipih; Boeristwati, Endry; Utami, Sintowati Rini (Erudio Journal of Educational Innovation, 2024)
Class 7 Indonesian language learning in the Kurikulum Merdeka aims to form students who are able to master language skills, one of which is writing skills. The linguistic aspect of fantasy story texts is an important part of teaching material in the learning process with the main aim of writing. Linguistic aspects are used as text characteristics and differences between texts. The aim of this research is to describe linguistic aspects in fantasy story texts. The method used in this research is a qualitative method with descriptive analysis and data collection techniques through literature studies obtained from various books, scientific articles, previous research, and data related to linguistic aspects of fantasy story texts. Apart from that, it's also done observations, interviews, and distribution of questionnaires to students and educators at SMP Negeri 78 Jakarta regarding linguistic aspects of fantasy story texts. The results of the research show that the linguistic aspects of fantasy story texts consist of the use of pronouns and people's names as a storytelling point of view, conjunctions or conjunctions to mark time order, words that are perceived by the five senses to describe the setting (place, atmosphere and time), choice of words with figurative and special meanings, words of surprise or expressions of surprise, use of figures of speech, direct and indirect sentences, spelling (use of letters, writing words, use of punctuation marks, and adjustments to writing absorption elements), and repetition.